A kinematical catalogue of HII regions and superbubbles in the LMC. (5th March 2015) - Ambrocio-Cruz, P.; Le Coarer, E.; Rosado, M.; Russeil, D.; Amram, P.; Laval, A.; Epinat, B.; Ramírez, M.; Odonne, M.; Goldes, G.
Abstract: We report the results of a kinematic Hα survey of the Large Magellanic Cloud (LMC) in the form of a kinematic and photometric catalogue of 210 HII regions, the radial velocity field of the ionized hydrogen in this galaxy, and the LMC Rotation Curve obtained from the velocity field. These data aim at understanding the LMC HII regions, bubbles and superbubbles in a global (galactic) scale so that we could have a 3D view and separate the rotation due to gravitational potential from other motions such as expansions.